Uma análise das inserções dos empréstimos linguísticos da área da informática no Dicionário Aurélio XXI - Prado, Daniela de Faria (2006)
This work searched reflection about the insertions of Loan Words from English language of Computing area in the Aurélio XXI dictionary. The theoretical model elected for the organization and analysis of the lexical units colected for us considered Guilbert (1975), Biderman (2001), Alves (1994) and Carvalho (1984). So, with teh aim of verify neological stage the lexical units are, as well, criterias for their insertion. After collecting of new words, which appear as portuguese units and as loan words. We have noticed a lack of criterias related to the insertion of units from an specilized area in a general language dictionary, what brings us the question of lexicographic production in Brazil do not count on established criterias and neither a language politics which deserves attention from studious and authorities. In the light of lexicography and lexicology we pointed out some incoherences in the organization of macro and microstructure of the work in study.